Evaluating The Impact Of Additional Employee Income (Tpp) On Civil Servant Teachers’ Performance: A Policy Analysis In Mimika Regency - Stefason, Stefanus; Mustofa, Amirul; Pramudiana, Ika Devy (Socious Journal, 2025)
This study evaluates the implementation of the Additional Employee Income (Tunjangan Penghasilan Pegawai or TPP) policy for civil servant teachers (Aparatur Sipil Negara – ASN) in Mimika Regency, Indonesia, using six public policy evaluation indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. A qualitative descriptive approach was employed, incorporating semi-structured interviews with education stakeholders and analysis of teacher attendance documentation from 2023 to 2024. The findings reveal substantial discrepancies in 2023 between biometric (fingerprint) attendance and compliance with instructional duties. For example, in SMK Negeri 3 Mimika, the fingerprint attendance rate was 90%, yet only 13% of teachers complied with teaching-hour requirements; similarly, SMP Negeri 3 recorded 78% attendance but only 12% compliance. Improvements were observed in 2024, with the attendance-compliance gap narrowing significantly e.g., SMK Negeri 1 Mimika (95% vs. 90%) and SD Inpres Timika V (90% vs. 88%). Despite these improvements, interviews indicate that the TPP policy has not led to meaningful enhancements in teaching quality, pedagogical innovation, or long-term commitment. The policy is perceived as inefficient due to bureaucratic rigidity, financially inadequate in relation to cost-of-living disparities, and insufficiently responsive to the structural challenges of remote and underserved schools. Consequently, policy reform is urgently required to ensure that the TPP system is performance-based, contextually adaptive, and aligned with the broader goals of public sector accountability and equitable education outcomes.